AB0922 Pulmonary Involvement in Connective Tissue Diseases - A Retrospective Analysis of A Multidisciplinary Approach. (10th June 2014) - Gonçalves, D.; Vieira, R.; Fonseca, R.; Abelha, J.; Terroso, G.; Madureira, P.; Bernardes, M.; Morais, A.; Costa, L.
Abstract : Background: The lung is a frequent target of connective tissue diseases (CTDs) and all components of the respiratory system are at risk. Interstitial lung disease (ILD) is frequently seen in CTDs, particularly rheumatoid arthritis (RA) and systemic sclerosis (SSc), and is a leading cause of significant morbidity and mortality. Non-specific interstitial pneumonia (NSIP) is the most common pattern in all CTDs, except for RA characterized by a higher frequency of usual interstitial pneumonia (UIP). A large percentage of patients with CTD-associated ILD has limited and stable disease, not requiring treatment. Objectives: To assess the lung injury during CTDs, with particular attention to ILDs, and examine high-resolution CT (HRCT) features, abnormalities in pulmonary function tests (PFT) as well as therapeutic approach. Methods: Retrospective analysis of patients discussed at meetings of Rheumatology and Pneumology in the last two years. Data collection was done through the informatics hospital records. We analyzed the HRCT, forced vital capacity (FVC) and DLCO divided by alveolar volume (DLCO/AV), 6 min walk test (6MWT) and arterial gasometry (AGS) of patients with CTD-associated ILD. We also analyzed the effects of cyclophosphamide (Cy) treatment on DLCO/AV, FVC and HRCT at 6 months. Results: 49 patients were analyzed. All were Caucasian and 38 were women. The most were non smoker (n=25). At the time of diagnosis of the DTC, the mean age was 46 years (SD 16.7). RA was the most common CTD in this group of patients, followed by SSc. Of the 49 patients, 4 were diagnosed with pulmonary disease before the diagnosis of CTD (mean 1.5 years before). Of the remaining 45 patients, the median duration of CTD was 4 years. Forty-four patients had abnormal HRCT findings; most commonly with reticular features consistent with lung fibrosis. Isolated ground-glass attenuations were identified in 16 patients. Of the 17 patients with RA, 10 had reticular pattern on HRTC. At diagnosis, the mean of DLCO/AV and FVC was 70.2% (SD 19.8) and 86.1% (SD 17.4) of the predicted value, respectively. Ten patients had values of DLCO/VA <60% (9 of these had lung fibrosis) and eight patients had FVC <70% predicted. Median desaturation in 6MWT was 5%. Of the 39 patients with known AGS, 15 had hypoxemia. Seven out of 49 patients showed increased systolic pulmonary artery pressure, estimated by echocardiography. In patients undergoing treatment due to ILD (n=12), the combination of corticosteroids with Cy was the treatment of choice. The median number of Cy cycles was 9 (min.3; max. 12). We typically evaluate the response to therapy every three - six months. Of the 9 patients who completed more than 6 cycles of Cy, only one had imaging deterioration. In the remaining patients (n=8) findings showed overlapping. Conclusions: Not every patient with CTD-ILD requires treatment and, in these diseases, halting progression and maintaining stability should be considered a success. It's important to distinguish trivial disease from clinically significant ILD and for this reason, the multidisciplinary approach of these patients, to a proper and early orientation, is essential. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5323